The mechanisms of politico-security regionalism in Southeast Asia and Southern Africa : a comparative case study of ASEAN and SADC - Schoeman, Maxi (University of Pretoria, 2013)
Thesis (DPhil (International Relations))--University of Pretoria, 2007.